Ventilation impairment of residents around a cement plant - Kim, Sul Ha; Lee, Chul Gab; Song, Han Soo; Lee, Hyun Seung; Jung, Min Soo; Kim, Jae Yoon; Park, Choong Hee; Ahn, Seung Chul; Yu, Seung Do (Annals of occupational and environmental medicine, 2015)
Objectives To identify adverse health effects due to air pollution derived from a cement plant in Korea. The ventilation impairment in residents around a cement plant was compared to another group through a pulmonary function test (PFT). Methods From June to August of 2013, both a pre and post-bronchodilator PFT was conducted on a “more exposed group (MEG)” which consisted of 318 people who lived within a 1 km radius of a cement plant and a “less exposed group (LEG)” which consisted of 129 people who lived more than 5 km away from the same plant. The largest forced expiratory volume in a one second (FEV1) reading and a functional residual capacity (FVC) reading were recorded after examining the data from all of the usable curves that were agreed upon as valid by PFT experts of committee of National Institute of Environmental Research. The global initiative for chronic obstructive lung disease (GOLD) criteria for COPD, defined the FEV1/FVC ratio < 0.7 as the obstructive type, and the FEV1/FVC ratio ≧ 0.7 and FVC% predicted < 80% were as the restrictive type. The FVC% predicted value was estimated using Korean equation. We compared the proportion of lung function impairments between the MEG and the LEG by using a chi-square, and estimated the OR of obstructive and restrictive ventilation impairments by logistic regression. Results The obstructive type impairment proportion was 9.7% in the MEG, whereas it was 8.5% in the LEG. The restrictive type was 21.6% in the MEG which was more than the 12.4% of the LEG. The odds ratio (OR) of total ventilation impairment in the MEG was 2.63 (95% CI 1.50 ~ 4.61) compared to the LEG. The OR of obstructive type in the MEG was 1.60 (95% CI 0.70 ~ 3.65), the smoking history was 3.10 (CI 1.10 ~ 8.66) whereas OR of restrictive type in the MEG was 2.55 (95% CI 1.37 ~ 4.76), the smoking history was 0.75 (95% CI 0.35 ~ 1.60) after adjusting for sex and age. Level of exposure to particulate played a role in both types. However, it appeared to be a significant variable in restrictive type, while smoking history was also an important variable in obstructive type. Conclusion Although this study is a limited cross-section study with a small number of subjects, ventilation impairment rate is higher in the MEG. There might be a possibility that it is due to long-term exposure to particulate dust generated by the cement plant.